Answer:
c) y−6=−2(x+2)
Step-by-step explanation:
The general point slope form equation is:
y - y1 = m*(x - x1)
where x and y are the variables, (x1, y1) is the coordinate of a point on the line and m is the slope of the line.
To calculate the slope of the line we need two points on the line (x1, y1) and (x2, y2) and the following equation:
m = (y2 - y1)/(x2- x1)
Coordinates of point A: (-2, 6)
Coordinates of point B: (2, -2)
Replacing into the equation:
m = (6 - (-2))/(-2 - 2)
m = 8/(-4)
m = -2
Replacing this value and coordinate of point A into the general point slope equation we get:
y - 6 = -2*(x - (-2))
y - 6 = -2*(x + 2)